1998
DOI: 10.1002/(sici)1097-010x(19980615)281:3<201::aid-jez5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating insulin and corticosterone concentrations during different reproductive phases and their relationships to body weight and androstenedione concentration of maleScotophilus heathi

Abstract: The aim of the present study was to determine the serum levels of insulin and corticosterone during different reproductive stages in a natural population of the male bat, Scotophilus heathi and their relationship to body weight and androstenedione level. Changes in body weight were marked by weight gain before winter dormancy and weight loss during winter dormancy. Circulating insulin level varied significantly over the season and correlated positively with changes in body weight and androstenedione level. Cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Although glycogen has an important role in energy homeostasis, several bat species rely mainly on lipid reserves to support reproductive activities (Kunz et al, 1998;Krishna et al, 1998;Srivastava and Krishna, 2007;2008). The data obtained here seem to indicate that lipid reserves of male M. molossus remained unaltered in all seasons, except for the adiposity index.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although glycogen has an important role in energy homeostasis, several bat species rely mainly on lipid reserves to support reproductive activities (Kunz et al, 1998;Krishna et al, 1998;Srivastava and Krishna, 2007;2008). The data obtained here seem to indicate that lipid reserves of male M. molossus remained unaltered in all seasons, except for the adiposity index.…”
Section: Discussionmentioning
confidence: 51%
“…It has been reported that insect-eating bats are able of fly while foraging powered by exogenous (dietary nutrients) rather than endogenous sources (glycogen or lipids) (Voigt et al, 2010). Reproductive activity in insect-eating bats also seems to require great energy expenditure, but this is based mainly on body lipid reserves stored during the previous seasons (Kunz et al, 1998;Krishna et al, 1998;Srivastava and Krishna, 2007;2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although glucocorticoid concentrations from these studies are clearly not baseline, because of the potentially large variation in the time individual animals have been in traps, it is difficult to interpret stress-induced concentrations. Nevertheless, most studies report seasonal differences in stress-induced glucocorticoid concentrations, but, as with baseline concentrations, some species, including male yellow-pine chipmunks (54), show a seasonal nadir during breeding (3,29,31,38,41,48), some, including golden-mantled ground squirrels (12), show a seasonal peak during breeding (1,11,30,48), and some, including female yellow-pine chipmunks (37), show no seasonal differences (2,10,28,69). In addition, most (7,16,52), but not all (49), captive studies with nontraditional laboratory animals show seasonal glucocorticoid variation.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma glucocorticoid measurement has been employed in numerous chiropteran studies (Krishna et al 1998, Srivastava and Krishna, 2008, Allen et al 2010, Lewanzik et al 2012. Studies of Pteropus species have found that cortisol is the primary glucocorticoid occurring in plasma (Widmaier and Kunz 1993, Widmaier et al 1994, b Reeder et al 2004, and that animals exhibit significant elevations in plasma glucocorticoid levels in response to restraint stress.…”
mentioning
confidence: 99%
“…Plasma glucocorticoid measurement has been employed in numerous chiropteran studies (Krishna et al 1998, Srivastava and Krishna, 2008, Lewanzik et al 2012, and cortisol is recognised to be the primary plasma glucocorticoid in Pteropus species Kunz 1993, Reeder et al 2006). …”
mentioning
confidence: 99%